2016
DOI: 10.1161/strokeaha.116.013007
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging of Plaque Morphology, Burden, and Distribution in Patients With Symptomatic Middle Cerebral Artery Stenosis

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
58
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 39 publications
6
58
0
Order By: Relevance
“…This suggests that type 2 thickening pattern may be a marker of more progressive and extensive plaques, which may easily develop into vulnerable plaques. This finding is in line with a previous study, in which the authors found that asymptomatic lesions were associated with eccentric plaques, but symptomatic lesions were both eccentric and concentric 7. However, their study included most patients with chronic stroke, which failed to accurately reflect the association between plaque features and acute stroke.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This suggests that type 2 thickening pattern may be a marker of more progressive and extensive plaques, which may easily develop into vulnerable plaques. This finding is in line with a previous study, in which the authors found that asymptomatic lesions were associated with eccentric plaques, but symptomatic lesions were both eccentric and concentric 7. However, their study included most patients with chronic stroke, which failed to accurately reflect the association between plaque features and acute stroke.…”
Section: Discussionsupporting
confidence: 90%
“…Also, a postmortem study found that neovascularity in intracranial atherosclerotic plaque is associated with infarct 28. Several studies of intracranial VWI have reported that plaque enhancement is associated with acute, subacute, and even chronic infarction 7, 15, 17, 29, 30. We found that strong contrast enhancement (grade 2) was associated with culprit lesions, likely suggesting greater neovascularization and/or inflammation activities in those lesions.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…45 Another study including symptomatic significant MCA stenosis showed that plaques with non-significant luminal narrowing was associated with eccentricity (p<0.05). 40 Therefore, the analysis of the …”
Section: Assessment Of Carotid Plaque Burden Using Ultrasonographymentioning
confidence: 99%